Recovery of Au(CN)2− by adsorption using reduced graphene oxide/ascorbic acid hydrogel. Issue 3 (3rd July 2018) - Sun, Kaige; Peng, Weijun; Zhang, Tianyi; Song, Shaoxian
ABSTRACT: A new kind of 3D material, reduced graphene oxide/ascorbic acid hydrogel (rGO/AAH), was used for the first time to recover the complex Au(CN)2 − ion from aqueous solution. The as-prepared rGO/AAH was characterised by XRD, FT-IR, SEM and EDS. The experimental results indicate that the adsorption isotherm data of Au(CN)2 − on rGO/AAH are well fitted by the Langmuir model, and the obtained maximum saturated adsorption capacity was up to 47.6 mg g −1 . The adsorption kinetics was well described by the pseudo-second-order kinetic model, indicating that the overall rate of Au(CN)2 − adsorption process is chemically controlled. In addition, the adsorption thermodynamics indicate that the adsorption process is spontaneous and exothermic. It is considered that the hexagonal rings of graphene in the rGO/AAH mainly contribute to the adsorption of the Au(CN)2 − complex.